N-3 PUFAs have beneficial effects on anxiety and cognition in female rats: Effects of early life stress. (August 2015) - Pusceddu, Matteo M.; Kelly, Philip; Ariffin, Nurbazilah; Cryan, John F.; Clarke, Gerard; Dinan, Timothy G.
Highlights: n-3 PUFAs reduce anxiety- and depressive-like behaviours in female rats. The positive anti-stress effects of n-3 PUFAs are associated with activation of glucocorticoid receptors. Maternal separation alters neuroendocrine, monoaminergic and, immune systems. The effects of maternal separation are not reversed by n-3 PUFAs. Abstract: Stressful life events, especially those in early life, can exert long-lasting changes in the brain, increasing vulnerability to mental illness especially in females. Omega-3 polyunsaturated fatty acids (n-3 PUFAs) play a critical role in the development and function of the central nervous system (CNS). Thus, we investigated the influence of an eicosapentaenoic acid (EPA)/docosahexaenoic acid (DHA) (80% EPA, 20% DHA) n-3 PUFAs mixture on stress-related behavioural and neurobiological responses. Sprague-Dawley female rats were subjected to an early-life stress, maternal separation (MS) procedure from postnatal days 2 to 12. Non-separated (NS) and MS rats were administered saline, EPA/DHA 0.4 g/kg/day or EPA/DHA 1 g/kg/day, respectively. In adulthood, EPA/DHA treated animals had a dose dependent reduction in anxiety in NS rats. Furthermore, cognitive performance in the novel object recognition task (NOR) was improved by EPA/DHA treatment in NS animals only. EPA/DHA 1 g/kg/day decreased behavioural despair in the forced swim test. Notably, EPA/DHA high dose increased the translocation of GRs into the nucleus of NS rat hippocampus. However, the levels of mBDNF remained unchanged in all the experimental groups. The corticosterone response to an acute stress was blunted in MS rats and this was further attenuated by pre-treatment with EPA/DHA. Immune response and monoamine neurotransmission were significantly altered by early-life stress. In conclusion, our study supports the view that n-3 PUFAs are beneficial in neurodevelopmentally normal animals but have little positive benefit in animals exposed to early life stress.